2015
DOI: 10.15448/1980-8623.2015.2.17642
|View full text |Cite
|
Sign up to set email alerts
|

As Atribuições de Causalidade no Ensino Fundamental: Relações com Variáveis Demográficas e Escolares

Abstract: RESUMOEste artigo tem como objetivo identificar as atribuições de causalidade para sucesso e fracasso escolar, bem como verificar se existem relações entre essas atribuições e variáveis como sexo, repetência, idade e escolaridade. Participaram do estudo 275 alunos do 5º ao 9º ano de uma escola pública de Minas Gerais. A coleta de dados foi realizada por meio de um Questionário Demográfico e de uma Escala de Avaliação das Atribuições de Causalidade para Sucesso e Fracasso Escolar. Os dados foram analisados de a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…In another study with the EAVAT-EF, students without a history of grade repetition obtained a higher score in the success causes, indicative of more internal and controllable causal loci of attributions by some of these students compared with those who had repeated. Attribution to causes for success was also identified in younger students (9 to 10 years) and those in elementary school (5th grade) (Garcia and Boruchovitch 2015).…”
Section: Introductionmentioning
confidence: 89%
“…In another study with the EAVAT-EF, students without a history of grade repetition obtained a higher score in the success causes, indicative of more internal and controllable causal loci of attributions by some of these students compared with those who had repeated. Attribution to causes for success was also identified in younger students (9 to 10 years) and those in elementary school (5th grade) (Garcia and Boruchovitch 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Focusing on intrapersonal causal attributions, which prospectively interfere with motivational quality, Miranda et al (2012) found that the explanatory contribution of this construct for students' performance from Portugal in Portuguese language and mathematics was greater for Primary Education (33 %) than for Secondary Education (21 %). In the studies by Garcia and Boruchovitch (2015) and , there was a greater indication of causal attributions for general school success than in the evaluation of samples from the first stage of Middle School to the second stage. Regarding SRL in the social sphere, at the beginning of schooling, Serafim and Boruchovitch (2010) found more negative perceptions about strategies to ask for help, while in the final years of Middle School, these differences were not observed, indicating that during the schooling, students become aware of the need to establish support networks as a way to optimize their learning.…”
mentioning
confidence: 93%
“…In contrast, those who had no history of repetition reported more attempts to solve problems alone, seeking help only when they considered it necessary. In terms of motivation, Garcia and Boruchovitch (2015) found that students who had not repeated a school year indicated more causal attributions aimed at school success. The same result was found in the study by , which also found more causal attributions for school failure on the part of non-failing students, indicative of the notions of commitment to academic performance, be it school success or failure, from the manifestation of controllable causes of internal locus.…”
mentioning
confidence: 99%
“…Considerando o ambiente escolar, o desempenho dos alunos, no contexto da aprendizagem, está associado a diversos fatores condicionantes, sendo a afetividade, a principal característica determinante ao desenvolvimento do sujeito. Sob a perspectiva de que o ensino básico, fundamental e médio forma a base para a continuidade do aprendizado na vida acadêmica (BNCC, 2019), é assustador a frequência em que a literatura aponta a prevalência de depressão, estresse e ansiedade em crianças no período escolar, indicando a influência que as emoções e a saúde, provocam no desenvolvimento escolar (Garcia & Boruchovitch, 2015…”
Section: Introductionunclassified